2020
DOI: 10.1021/acs.jafc.0c01943
|View full text |Cite
|
Sign up to set email alerts
|

Toxicokinetic Studies in Piglets Reveal Age-Related Differences in Systemic Exposure to Zearalenone, Zearalenone-14-Glucoside, and Zearalenone-14-Sulfate

Abstract: Juveniles are considered as one of the most vulnerable population groups concerning mycotoxins and their modified forms. The weaning stage is a particularly vulnerable period in the life of mammals, reflected in intestinal and immune dysfunction. The current study investigated the toxicokinetic (TK) characteristics of zearalenone (ZEN), zearalenone-14-glucoside (ZEN14G), and zearalenone-14-sulfate (ZEN14S) in weaned (4-week-old) piglets, by means of oral and intravenous administration of equimolar doses, i.e.,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 33 publications
1
13
0
Order By: Relevance
“…These results were consistent with those of previously published studies performed on crossbreed pigs. , However, several studies reported relatively low conjugation rates of ZEN and ZOLs in urine with a wide range of values, ranging from 27 to 94% and 23 to 93% . Many studies revealed that a variety of factors could influence ZEN metabolism, including animal species, breed, gender, age, physiological status, individual difference, and so on. ,, The minipig appears to have a higher rate of phase I and phase II metabolic activities for ZEN compared to the crossbred pigs, resulting in conjugated [ZEN + α-ZOL] in plasma being the potential bioindicator of ZEN exposure in minipigs. It is possibly due to genetic differences between experimental pigs employed in the present study and previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…These results were consistent with those of previously published studies performed on crossbreed pigs. , However, several studies reported relatively low conjugation rates of ZEN and ZOLs in urine with a wide range of values, ranging from 27 to 94% and 23 to 93% . Many studies revealed that a variety of factors could influence ZEN metabolism, including animal species, breed, gender, age, physiological status, individual difference, and so on. ,, The minipig appears to have a higher rate of phase I and phase II metabolic activities for ZEN compared to the crossbred pigs, resulting in conjugated [ZEN + α-ZOL] in plasma being the potential bioindicator of ZEN exposure in minipigs. It is possibly due to genetic differences between experimental pigs employed in the present study and previous studies.…”
Section: Discussionsupporting
confidence: 90%
“…A different experiment, using a considerably lower toxin dose (15.1 µg/kg BW for ZEN-14G and 12.5 µg/kg BW for ZEN-14S), reported that ZEN-14S was not present in urine following oral administration. In the study, the urine also contained ZEN, which indicated the hydrolysis of ZEN-14S [132,134,135]. Low bioavailability of α-ZOL and α-ZOL-14G was observed in rats, which can be explained by their efficient metabolism within the GI system [28,133].…”
Section: Studies In the In Vivo Systemsmentioning
confidence: 98%
“…Among these mycotoxins, fumonisin B, ochratoxin A, zearalenone (ZEN), and aflatoxin B1 are appearing extensively in cereals such as soybean, sorghum, corn, oat, and rice and their by-products, and further as residues and metabolites in animal food. , The occurrence of these mycotoxins in animal feed is one of the main issues in animal husbandry owing to the poisonous effect of these mycotoxins observed in animals. In particular, ZEN can cause serious effects, like dysfunction of the nervous system, cancer, and immunotoxicity. , ZEN cytotoxicity truly influences the proliferation, insusceptibility, endocrine activities, and animal inheritance, and stimulates human sex function. , Albeit, the toxicity of ZEN is moderately low (oral LD 50 value = 2g/kg) after oral intake by animals; it has been associated with cervical malignant growth in humans, early adolescence, and hyperplasic and neoplastic endometrium development. , Thus, the International Agency for Research on Cancer (IARC) has categorized ZEN as a group 3 carcinogen . Furthermore, several nations, for instance, Austria, Bulgaria, France, Hungary, Italy, Mexico, Armenia, Ukraine, and Latvia, have set the cutoff limits for ZEN from 0.02 to 1000 μg/kg in natural and prepared cereals to circumscribe the hazard to the people and animals .…”
Section: Introductionmentioning
confidence: 99%
“…2,3 ZEN cytotoxicity truly influences the proliferation, insusceptibility, endocrine activities, and animal inheritance, and stimulates human sex function. 4,5 Albeit, the toxicity of ZEN is moderately low (oral LD 50 value = 2g/kg) after oral intake by animals; it has been associated with cervical malignant growth in humans, early adolescence, and hyperplasic and neoplastic endometrium development. 6,7 Thus, the International Agency for Research on Cancer (IARC) has categorized ZEN as a group 3 carcinogen.…”
Section: ■ Introductionmentioning
confidence: 99%